Somatic Embryogenesis in Selected Conifer Trees Pinus nigra Arn. and Abies Hybrids - Salaj, Terézia; Klubicová, Katarína; Matusova, Radoslava; Salaj, Ján (Frontiers in Plant Science, 2019)
Somatic embryogenesis has been achieved in conifer trees Pinus nigra Arn. and in hybrids Abies alba x A. cephalonica, Abies alba x A. numidica. For intitiation of embryogenic tissues in Pinus nigra immature zygotic embryos enclosed in megagametophytes have been used. The initiated embryogenic cultures have been maintained and proliferated on solid culture medium DCR supplemented with 9 µM 2,4-D and 2.2 µM BA. Microscopic investigations revealed the presence of bipolar early somatic embryos in proliferating tissues. Suspension cultures have also been established by resuspending the embryogenic tissues in liquid culture medium. Experimentation with abscisic acid concentration resulted in successful somatic embryo maturation. Besides abscisic acid, the carbohydrate content or higher concentration of gelling agent in maturation medium were also important requirements for somatic embryo maturation. Germination of cotyledonary somatic embryos occurred on hormone-free medium and terminated in somatic seedlings regeneration. The regenerated somatic seedlings were transferred to soil and were capable of successful development. For initiation of embryogenic tissues in Abies hybrids juvenile explants as immature or mature zygotic embryos as well as cotyledons have been used and 4.4 µM BA as sole hormone was sufficient. Medium of the same composition was also convenient for their long-term maintenance. Maturation of somatic embryos has been achieved on solid DCR medium supplemented with 38 µM abscisic acid, polyethylene glycol (0, 5, 7.5, 10% PEG-4000) and different carbohydrates as maltose, sucrose, glucose (each 3%). PEG-4000 stimulated somatic embryo development in dependence of the carbohydrate source used. The cotyledonary somatic embryos germinated after desiccation treatment and the regenerated somatic seedlings have been transferred to soil. Cryopreservation of embryogenic tissues could be an alternative method for long-term maintenance. For cryopreservation the slow-freezing method was used with success. Tissue regeneration in post thaw period was relatively high and the regenerated tissues produced mature somatic embryos and subsequently plantlets. The embryogenic tissues have also been included in the experiments focused on genetic transformation either by biolistic (Pinus nigra) or Agrobacterium-mediated (Abies hybrids) methods. Proteomic study was performed to get deeper insight into the early stages of Pinus nigra somatic embryogenesis.